2017
DOI: 10.1097/moh.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Current status of blood ‘pharming’: megakaryoctye transfusions as a source of platelets

Abstract: Purpose of review Donor-derived platelets have proven to be of hemostatic value in many clinical settings. There is a fear that the need for platelets may outgrow the donor pool in first-world countries. Moreover, there are other challenges with donor platelets that add to the impetus to find an alternative platelet source, especially after the megakaryocyte cytokine thrombopoietin was identified. Megakaryocytes have since been differentiated from numerous cell sources and the observed released platelet-like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The fourth problem relates to recent initiatives to develop donor-independent sources of platelets to treat patients with thrombocytopenia. The need for such sources is emerging in developed countries due to steadily rising platelet demands coupled with restricted donor supplies [25]. Recent refinements in ex vivo culture of Mk derived from a variety of sources have enhanced feasibility of producing bioactive platelets or Mk for transfusion [25, 26].…”
Section: Clinical Significance Of the Infantile Megakaryocyte Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…The fourth problem relates to recent initiatives to develop donor-independent sources of platelets to treat patients with thrombocytopenia. The need for such sources is emerging in developed countries due to steadily rising platelet demands coupled with restricted donor supplies [25]. Recent refinements in ex vivo culture of Mk derived from a variety of sources have enhanced feasibility of producing bioactive platelets or Mk for transfusion [25, 26].…”
Section: Clinical Significance Of the Infantile Megakaryocyte Phenotypementioning
confidence: 99%
“…The need for such sources is emerging in developed countries due to steadily rising platelet demands coupled with restricted donor supplies [25]. Recent refinements in ex vivo culture of Mk derived from a variety of sources have enhanced feasibility of producing bioactive platelets or Mk for transfusion [25, 26]. A major limiting factor in this process is the poor proliferative capacity of adult type Mk in culture, despite efficient platelet biogenesis.…”
Section: Clinical Significance Of the Infantile Megakaryocyte Phenotypementioning
confidence: 99%
“…The therapeutic impact of PLPs has been well documented; for example, PLPs have shown the ability to improve wound healing [28,29]. Several groups have suggested that non-donor-based platelets derived from in vitro-grown megakaryocytes may serve as supplements to donor-derived platelets [30]. While the therapeutic potentials of nucleus-free PLPs have been previously demonstrated, the majority of the studies are limited to the applications of "mimicking platelet functions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that, in patients with liver failure, TPO plays a critical role in thrombocytopenia and in the restoration of platelet count after liver transplantation. Gollomp et al [ 6 ] found similar serum TPO levels before and after liver transplantation, as well as significantly lower TPO mRNA expressions in the liver tissues of patients with cirrhosis. Thrombocytopenia in patients with liver failure is challenging.…”
Section: Introductionmentioning
confidence: 99%